A Simple Cu(II) Polyelectrolyte as a Method to Increase the Work Function of Electrodes and Form Effective p‐Type Contacts in Perovskite Solar Cells. (4th March 2021) - Ali, Azmat; Ahn, Yohan; Khawaja, Kausar Ali; Kang, Ju Hwan; Park, Yu Jung; Seo, Jung Hwa; Walker, Bright
Abstract: One effective strategy to improve the performance of perovskite solar cells (PSCs) is to develop new hole transport layers (HTLs). In this work, a simple polyelectrolyte HTL, copper (II) poly(styrene sulfonate) (Cu:PSS), which comprises easily reduced Cu 2+ counter‐ions with an anionic PSS polyelectrolyte backbone is investigated. Photoelectron spectroscopy reveals an increase in the work function of the anode and upward band bending effect upon incorporation of Cu:PSS in PSC devices. Cu:PSS shows a synergistic effect when mixed with polyethylenedioxythiophene: polystyrenesulfonate (PEDOT:PSS) in various proportions and results in a decrease in the acidity of PEDOT:PSS as well as reduced hysteresis in completed devices. Cu:PSS functions effectively as a HTL in PSCs, with device parameters comparable to PEDOT:PSS, while mixtures of Cu:PSS with PEDOT:PSS shows greatly improved performance compared to PEDOT:PSS alone. Optimized devices incorporating Cu:PSS/PEDOT:PSS mixtures show an improvement in efficiency from 14.35 to 19.44% using a simple CH3 NH3 PbI3 active layer in an inverted (P‐I‐N) geometry, which is one of the highest values yet reported for this type of device. It is expected that this type of HTL can be employed to create p ‐type contacts and improve performance in other types of semiconducting devices as well. Abstract : A simple, solution‐processed, highly transparent, and cost‐effective polyelectrolyte hole transport layer (HTL) consisting of copper (II) poly(styrene sulfonate) (Cu:PSS) is introduced and employed in inverted perovskite solar cells. Easily reduced Cu 2+ counter‐ions balance the negative charges on the PSS polyelectrolyte backbone, supporting p ‐doping at the interface with the perovskite and Cu:PSS and allowing efficient extraction of p ‐type carriers at the anode.